Finanças comportamentais: estudo do comportamento do investidor - Leite, Luciara Braga (2014)
Among the main issues that are being debated in Finance is the validity of the assumptions made for its more traditional theories, in particular the rationality of economic agents. In this context, many works have emerged with the aim of improving the dominant theoretical models incorporating behavioral aspects before disregarded. These lines of research have led to a promising new field of study called behavioral finance. This bibliographic research seeks to demonstrate satisfactory attempt at explaining a range of phenomena regularly observed in financial markets and incompatible with the predictions of traditional models. The first stage of the work covers the introduction, objectives and rationale for conducting the same. The second stage consists of a literature review on the subject by proposing an interaction between theories and points out the main concepts of Behavioral Finance. The third step describes the methodology. In the fourth stage the results: with the evidence of the behavior model availability. Finally, conclusions and suggestions for future studies in the Brazilian context.